Peran Self-Efficacy Akademik terhadap Resiliensi Akademik pada Mahasiswa Tahun Pertama - Nurul Afifah; Rozi Sastra Purna; Liliyana Sari (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2022)
Academic resilience becomes an important psychological factor that can help first-year undergraduate students in facing various challenges in the early period of university. Some researchers reported that self-efficacy has a role in the formation of resilience in individuals. The present study attempted to investigate the role of academic self-efficacy in academic resilience among the first-year undergraduate students. A total of 400 students (61.75% female) in Universitas Andalas were recruited as research subjects through the purposive sampling technique. Measures used in the study were the Academic Resilience Scale-30 (ARS-30) adapted from Cassidy (2016) and the Academic Self-efficacy Scale was constructed based on the theory of Bandura (1997). The simple linear regression analysis results showed that academic self-efficacy had a significant and positive effect on academic resilience by about 60.2%. Therefore, the level of academic self-efficacy among first-year undergraduate students had an important role in increasing the level of academic resilience in facing the university life. In addition, the current study also found that students in this research had a moderate level of academic self-efficacy and academic resilience. Keywords: Academic Resilience; Academic Self-Efficacy; First-Year Undergraduate Students